ChemInform Abstract: Debenzylative Cycloetherification: An Overlooked Key Strategy for Complex Tetrahydrofuran Synthesis. Issue 37 (August 2016) - Tikad, Abdellatif; Delbrouck, Julien A.; Vincent, Stephane P.
Abstract: Review: [73 refs.